2022
DOI: 10.1002/phar.2671
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of inactivated vaccines in patients treated with immunosuppressive drug therapy

Abstract: Inactivated vaccines are generally considered safe in immunocompromised patients but the ability of immunocompromised patients to generate an effective immune response to vaccines is uncertain. Although recent reviews have focused on the effects of vaccines in patients who are immunocompromised due to various disease states (primary immunodeficiency), the effects of immunosuppressive drug therapy (secondary immunodeficiency) has received relatively less attention. This review evaluates evidence regarding the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Several studies showed an impaired vaccine immunogenicity in patients under immunosuppressive therapy, suggesting the need of a “drug washout” period or drug suspension prior to the vaccine administration. As the temporal window between the last immunosuppressive drug dose and vaccine administration is variable according to the ongoing pharmacological therapy, and could be as long as 6-12 months for rituximab, vaccination schedule should be tailored to the patient clinical context, according to the treating physician judgement, with the aim to achieve the better balance between individual patient risk of contracting vaccine preventable infections and the risk of under-treating the underlying autoimmune disease ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an impaired vaccine immunogenicity in patients under immunosuppressive therapy, suggesting the need of a “drug washout” period or drug suspension prior to the vaccine administration. As the temporal window between the last immunosuppressive drug dose and vaccine administration is variable according to the ongoing pharmacological therapy, and could be as long as 6-12 months for rituximab, vaccination schedule should be tailored to the patient clinical context, according to the treating physician judgement, with the aim to achieve the better balance between individual patient risk of contracting vaccine preventable infections and the risk of under-treating the underlying autoimmune disease ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inactivated vaccines are safe to deliver while taking immunosuppressives or immunomodulators and should be encouraged. 8 However, vaccine response may be compromised. 5 In this study, we investigate vaccination status and documentation of vaccine counseling in an academic pediatric dermatology practice before prescribing immunosuppressives or immunomodulators.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, inactivated vaccines are safe to deliver while taking immunosuppressives or immunomodulators and should be encouraged 8 . However, vaccine response may be compromised 5 .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Inactivated vaccines comprise killed pathogens losing pathogenicity and retaining antigenicity, activating a hu-moral immune response against the corresponding pathogens. 20,21 Our previous study showed that COS as an adjuvant of the Vibrio harveyi formalin-killed cells (FKC) vaccine notably enhanced the immune protective effect of FKC. 22,23 However, the mechanism of COS enhancing FKC effectiveness against V. harveyi in grouper is unclear.…”
Section: Introductionmentioning
confidence: 99%